Marjorie Claire Stinson papers - Stinson, Marjorie Claire, 1896-1975.
Correspondence, research notes, biographical material, financial records, printed matter, and other papers relating principally to Stinson's role and experiences in early aviation. Also includes material relating to aviation in World War I; the Stinson Flight School in San Antonio, Tex.; the Early Birds of Aviation club; the Aero Club of America; her sister, Katherine Stinson (Otero); her brother, Edward Stinson; and other Stinson (Stimson) family members.
Library of Congress Prints and Photographs Division.
Aviator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Stinson, Edward, -- 1893-1932.; Stinson, Katherine, -- 1891-1977.; Stimson family; Aero Club of America; Early Birds of Aviation (Organization); Stinson Flight School (San Antonio, Tex.); Aeronautics; Aeronautics -- Societies, etc; Flight schools -- Texas -- San Antonio; World War, 1914-1918 -- Aerial operations; Aviators